Morphology of jaw ligaments and its role in the cranial kinesis of the domestic turkey (Meleagris gallopavo) - S, Venkatesan.; Nissar, Shazia; Basha, Sabiha Hayath; Kannan, T. A.; Ramesh, Geetha (Indian Journal of Veterinary Anatomy, 2016)
The turkeys are opportunistically omnivorous birds which occur in a variety of geographic areas and diverse habitats and possess variable feeding habits according to the season, age and geography. The aim of the present study is to investigate the morphology of the jaw ligaments and their possible role in the cranial kinesis in the turkey. Eight adult turkey heads were dissected out and studied for the ligament morphology. The length and width of the ligaments were measured and presented. The four jaw ligaments viz., post orbital ligament, medial and lateral jugulo-mandibular ligaments and occipito-mandibular ligament were observed in the present study. The post orbital ligament was very well-developed and considered to play a crucial role in the coupled kinesis. The medial jugulo-mandibular ligament possessed only a cranial part with one meniscus. The medial and lateral jugulo-mandibular ligament reinforced the quadratomandibular and quadrate-quadratojugal joints. The occipito-mandibular ligament was very strong and acted as the chief stabiliser of the jaw apparatus.